Structural Design of Mechanical Property for Biodegradable Polymeric Stent - Yunbo Wei; Minjie Wang; Danyang Zhao; Hongxia Li; Yifei Jin (Advances in Materials Science and Engineering)
How to improve stent mechanical properties is a key issue for designing biodegradable polymeric stents (BPSs). In this study, a new design method of BPS was proposed based on the force analysis of supporting rings and bridges during stent implantation, and a novel BPS called open C-shaped stent (OCS) with superior comprehensive mechanical properties was developed accordingly. The key mechanical properties including radial force, radial recoil, and axial foreshortening of the OCS have been comprehensively studied and compared with those of the Abbott BVS using finite element analysis (FEA). In addition, the effects of the stent geometries on these mechanical properties have also been discussed in detail. Besides, in vitro mechanical tests including stent expansion and planar compression experiments have been performed to verify the simulation results. Based on the FEA results, it is found that the radial force and radial recoil of the designed OCS are 30% higher and 24% lower than those of the BVS, respectively. Meanwhile, the OCS is not shortened during expansion. Radial force and radial recoil are mainly dependent on the supporting ring structure, and the utilization of designed unequal-height supporting ring (UHSR) can effectively improve these two properties. Axial foreshortening is mainly determined by the bridge geometry as well as the connecting position of the bridge with the adjacent supporting rings. It is feasible to improve the axial foreshortening by using the bridges with a curved structure and locating the connecting position in the middle of the straight section of the supporting elements. The rationality of the proposed OCS and the effectiveness of the finite element method have been verified by in vitro experiments.